Teacher Career Development Teacher Protection and Reward - Mahardika, Fadia; Sabila, Putri; Juangsih, Rina (Interdisciplinary Explorations in Research Journal, 2023)
Teachers are the main pillars in shaping the future of society and the younger generation. This paper describes three important aspects in the context of education: career development, protection and respect for teachers. Teacher career development is a key tool in improving teacher competencies. Teachers must have access to training and resources that allow them to keep up with modern education. Teacher protection is essential in covering physical, mental and social aspects. Teachers should work in a safe and supportive environment. Rewarding teachers plays a big role in increasing motivation and dedication for teachers. Rewards can be in the form of salary increases, public recognition, or respect for the teaching profession. The method used was to review several articles and journals related to teacher career development, protection and reward. Therefore, the quality of education can be improved with the quality of teachers who meet the standardization and create a more educated and inspired generation.